Delusional health beliefs. (June 2019) - May, Peter
Delusional health beliefs can be difficult and costly for practitioners to diagnose and manage. Patients often deny that mental distress is the cause of their illness, when it may be the most significant factor. Such patients can be relentless in their pursuit of a physical cause and go from doctor to doctor to find one who agrees with them, using up significant NHS resources. The number of negative investigations increases year on year, with the patient being referred back to their general practitioner without a working diagnosis. The recent publication of Susanne O'Sullivan's book, "It's All in your Head – True Stories of Imaginary Illness", shines a bright and necessary light on the difficulties of getting these patients to accept that their problems originate in their minds. Doctors, alerted by fat files, may be well advised to question any previous diagnosis, if it is not borne out by physical evidence and does not conform to known diagnostic criteria and disease patterns. In this context, it is timely to consider the true cause of Stephen Hawking's illness, which he has called into question in his last book, published after his death. Allegedly, he had been suffering from motor neurone disease, diagnosed when he was a very young man.Yet he survived to the age of 76, albeit in his later years in an increasingly crippled and distressed state. Such longevity is totally inconsistent with MND. What then was the cause of Hawking's illness? Is there any firm evidence that a consultant neurologist ever made that diagnosis, and on what grounds? The interplay between mind and body is mysterious and complex, but we need to question every symptom, if it is not grounded in objective reality.